Pile Construction Optimization for the Štefanići Landslide Remediation in Istria (Proceedings of Faculty of Civil Engineering, 2022)
The article describes the process of structure selection for the remediation of the Štefanići landslide in Istria based on parametric analyzes of the pile construction. The varied parameters are the diameter and the axial spacing of piles, so that ultimately six variants of pile constructions were analyzed. Stability analyzes as well as stress deformation analyzes were carried out using the Rocscience software package. Based on the results of the performed analyzes, the optimal pile construction was selected for which the landslide remediation project was developed. The article analyzes influence of the pile parameter variation on the behavior of the pile construction using the example of the Štefanići landslide remediation.
Keywords: landslide; remediation; pile construction; parametric analyzes